Catheter ablation of atrioventricular nodal reentrant tachycardia with an irrigated contact‐force sensing radiofrequency ablation catheter. (14th February 2023) - Panday, Priya; Holmes, Douglas; Park, David S.; Jankelson, Lior; Bernstein, Scott A.; Knotts, Robert; Kushnir, Alexander; Aizer, Anthony; Chinitz, Larry A.; Barbhaiya, Chirag R.
Abstract: Introduction: Radiofrequency ablation (RFA) slow pathway modification for catheter ablation of atrioventricular nodal reentrant tachycardia (AVNRT) is traditionally performed using a 4‐mm nonirrigated (NI) RF ablation catheter. Slow pathway modification using irrigated, contact‐force sensing (ICFS) RFA catheters has been described in case reports, but the outcomes have not been systematically evaluated. Methods: Acute procedural outcomes of 200 consecutive patients undergoing slow pathway modification for AVNRT were analyzed. A 3.5‐mm ICFS RFA catheter (ThermoCool SmartTouch STSF, Biosense Webster, Inc.) was utilized in 134 patients, and a 4‐mm NI RFA catheter (EZ Steer, Biosense Webster, Inc.) was utilized in 66 patients. Electroanatomic maps were retrospectively analyzed in a blinded fashion to determine the proximity of ablation lesions to the His region. Results: The baseline characteristics of patients in both groups were similar. Total RF time was significantly lower in the ICFS group compared to the NI group (5.53 ± 4.6 vs. 6.24 ± 4.9 min, p  = 0.03). Median procedure time was similar in both groups (ICFS, 108.0 (87.5–131.5) min vs. NI, 100.0 (85.0–125.0) min; p  = 0.2). Ablation was required in closer proximity to the His region in the NI group compared to the ICFS group (14.4 ± 5.9 vs. 16.7 ± 6.4 mm, respectively, p  = 0.01). AVNRT was rendered noninducible in all patients, and there was no arrhythmia recurrence during follow‐up in both groups. Catheter ablation was complicated by AV block in one patient in the NI group. Conclusion: Slow pathway modification for catheter ablation of AVNRT using an ICFS RFA catheter is feasible, safe, and may facilitate shorter duration ablation while avoiding ablation in close proximity to the His region.